Integration of banks and insurance companies activities in Ukraine - Zharikova , Оlena; Cherkesenko , Kateryna (Social Development and Security, 2021)
The article reveals the essence of modern bancassurance and new challenges and prospects for its development in Ukraine. The definition of “bancassurance” is theoretically substantiated and the general financial and economic characteristics of Ukrainian banks is given. The normative indicators of commercial institutions are analyzed along with the main risks affecting banking and insurance activities, the possibility of their leveling are determined. The study provides theoretical and practical information on the process of banks capital of and insurance companies merging, financial and economic analysis of JSC PrivatBank – one of the largest banks in modern Ukraine, and the assessment of the financial stability of its insurance partners. The insurance Ukrainian market study concerning the detection of possible prospects for cooperation with the studied bank was done. The calculations suggest that PrivatBank can cooperate with the leading insurance companies, such as AXA Insurance and Providna recommended as new partners. It is established that bancassurance technologies have a significant place at the current stage of development of the domestic financial market. Using a large customer base and a wide network of branches and outlets, banking experts expect that revenues from the sale of insurance products in 2021 may amount to 15% of total bank revenues, as the volume of bank insurance in JSC CB PrivatBank is growing quite rapidly. The activity of banks in market conditions is subject to its general laws, and therefore requires the development of a viable mechanism for managing financial activities, aimed at increasing the competitiveness of banks. Thus, the ability of bank managers to determine the degree of financial stability of their bank as well as that of the competing banks and counterparties is essential in making decisions. Therefore, the search for ways to optimize the financial condition of the bank is one of the principles of further rapid development of the banking system in Ukraine.